2018
DOI: 10.17221/34/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc sources and levels on zinc bioavailability, blood parameters, and nutrient balance of male mink (Neovison vison)

Abstract: . (2018): Effects of zinc sources and levels on zinc bioavailability, blood parameters, and nutrient balance of male mink (Neovison vison). Czech J. Anim. Sci., 63, 174-181.The objective of this study was to investigate the effects of different sources and levels of zinc (Zn) on nutrient digestibility, plasma metabolites, and relative Zn bioavailability in male mink. Animals in the control group were fed a basal diet, consisting mainly of corn, soybean oil, meat and bone meal, and fish meal, with no Zn supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…However, due to its low absorption rate, unstable chemical properties, and environmental pollution capacity, IOZ has been gradually replaced by organic zinc (OZ), which has good palatability, high chemical stability, lipophilicity, and bioavailability [6,7]. Previous studies have shown that the addition of OZ to feed (protein zinc, amino acid chelated/complexed zinc, and polysaccharide zinc [8,9]) can alleviate diarrhea [10], improve immune function [11] and antioxidant capacity [12], promote intestinal health [13], and enhance reproductive performance [14], thus supporting the healthy growth of animals.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its low absorption rate, unstable chemical properties, and environmental pollution capacity, IOZ has been gradually replaced by organic zinc (OZ), which has good palatability, high chemical stability, lipophilicity, and bioavailability [6,7]. Previous studies have shown that the addition of OZ to feed (protein zinc, amino acid chelated/complexed zinc, and polysaccharide zinc [8,9]) can alleviate diarrhea [10], improve immune function [11] and antioxidant capacity [12], promote intestinal health [13], and enhance reproductive performance [14], thus supporting the healthy growth of animals.…”
Section: Introductionmentioning
confidence: 99%